Estimated assessment of dietary exposure to artificial sweeteners from processed food in Nanjing, China. Issue 7 (3rd July 2021) - Wang, Yanli; Li, Chengguo; Li, Dengkun; Yang, Huamei; Li, Xiaocheng; Jin, Di; Xie, Wei; Guo, Baofu
ABSTRACT: The objective of this study was to measure the concentrations of three intensity sweeteners (Acesulfame–K, cyclamate and saccharin) in different categories of food available on the Nanjing market, and to investigate whether the Nanjing general population was at risk for exceeding the ADI of sweeteners. A set of 1885 foods was collected and analysed using the National Food Safety Standard procedure in order to establish the concentration levels of the sweeteners. Dietary exposure was estimated using probabilistic modelling software and compared directly with each sweetener's ADI. Consumption data from the China National Nutrition and Health Survey (conducted in 2010-2013) and the actual concentrations of sweeteners in the collected food products were used to perform the intake assessment. The results indicated that Acesulfame-K and cyclamate were commonly used in processed food, and processed nuts, preserved fruit, beverages, and bakery products are the main sources of sweeteners in Nanjing. The estimated exposure of sweeteners in Nanjing was well below the ADIs, as relative intakes at the 95th percentile were 29.7% for saccharin, 79.8% for cyclamate, and 35.9% for Acesulfame-K of the respective ADIs. It was concluded that adults were not at risk of exceeding ADIs for these sweeteners, but the intake of cyclamate at the higher percentiles by children may approach or slightly exceed ADI values.